Divergence time and species delimitation of microbivalves in the Southern Ocean: the case of Kidderia species - Levicoy, Daniela; Rosenfeld, Sebastian; Cardenas, Leyla (My University, 2021)
The systematics of Subantarctic and Antarctic near-shore marine benthic invertebrates requires major revision and highlights the necessity to incorporate additional sources of information in the specimen identification chart in the Southern Ocean (SO). In this study, we aim to improve our understanding of the biodiversity of Kidderia (Dall 1876) through molecular and morphological comparisons of Antarctic and Subantarctic taxa. The microbivalves of the genus Kidderia are small brooding organisms that inhabit intertidal and shallow subtidal rocky ecosystems. This genus represents an interesting model to test the vicariance and dispersal hypothesis in the biogeography of the SO. However, the description of Kidderia species relies on a few morphological characters and biogeographic records that raise questions about the true diversity in the group. Here we will define the specimens collected with genetic tools, delimiting their respective boundaries across provinces of the SO, validating the presence of two species of Kidderia. Through the revision of taxonomic issues and species delimitation, it was possible to report that the Antarctic species is Kidderia subquadrata and the species recorded in the Subantarctic islands Diego Ramirez, South Georgia and the Kerguelen Archipelago is Kidderia minuta. The divergence time estimation suggests the origin and diversification of Kidderia lineages are related to historical vicariant processes probably associated with the separation of the continental landmasses close to the late Eocene.
Keywords: cyamiidae; microbivalves; phylogeny; antarctic; subantarctic islands